Menilik Tradisi Megibung di Desa Budakeling, Kecamatan Bebandem, Kabupaten Karangasem, Provinsi Bali - Mahayani, Ni Kadek Gita Ginanti; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 2 No 01 (2022): JISSOROT, 2022)
Megibung in Budakeling Village is still stable until now. There is an effort to preserve the megibung culture and tradition by the village which is then regulated in the village awig-awig. Through this explanatory descriptive research, the philosophical values ??of Balinese Hindu community life such as menyama braya, the concept of joy and sorrow. Manggala karya will meebat and hold megibung. For humans yadnya, megibung can be done more than once, while for gods megibung yadnya only done once. Weber's theory of social action in megibung can be analyzed with four social actions. These are classified based on the background of the megibung implementation, the values ??contained in the megibung implementation, the factors that encourage individuals to take megibung actions. The moment of implementing the megibung tradition is one of the media that can integrate the Budakeling Village community which is dominated by Hindu-Balinese beliefs with its chess culture.